Attenuated cardiovascular reserve during prolonged submaximal cycle exercise in healthy older subjects - Correia, Luis C.L; Lakatta, Edward G; O’Connor, Frances C; Becker, Lewis C; Clulow, Jon; Townsend, Susan; Gerstenblith, Gary; Fleg, Jerome L (Journal of the American College of Cardiology, 2002)
The goal of this study was to determine the effect of age on the hemodynamic response to prolonged submaximal aerobic exercise in healthy volunteers. Reductions in peak work rate, heart rate (HR), and left ventricular (LV) emptying but higher blood pressure (BP) and systemic vascular resistance occur in healthy older versus younger humans during short bursts of graded maximal aerobic exercise. However, the effect of aging on the cardiovascular response to prolonged exercise at submaximal work rates typical of daily aerobic activities remains unknown. We evaluated cardiovascular performance throughout prolonged submaximal upright cycle ergometry in 40 carefully screened healthy untrained volunteers, 8 men and 12 women <50 years old, mean = 37 ± 8 years (younger), and 10 men and 10 women ≥50 years old, mean = 66 ± 9 years (older), during upright cycle exercise at 70% of peak cycle oxygen consumption (VO2) to exhaustion or a maximum of 120 min. Cardiac volumes were acquired by gated blood pool scans with 99mTc at rest and every 10 min throughout exercise. Duration of exercise was similar in younger ([81 ± 28 min] versus older [71± 29 min] subjects, p = NS). At 10 min of exercise in the steady state, older subjects demonstrated lower VO2 (1.1 ± 0.2 l/min vs. 1.3 ± 0.3 l/min) and lower HR (118 ± 17 vs. 135 ± 11 beats/min, p < 0.001) but larger end-diastolic (80 ± 11 ml/m2 vs. 73 ± 8 ml/m2, p = 0.03) and end-systolic volume index (ESVI) 20 ± 6 ml/m2 vs. 17 ± 4 ml/m2, p < 0.05) than younger ones. Between 10 min and exercise termination, with VO2 held constant in both groups, increases in HR (14.0 ± 12.4 beats/min vs. 5.9 ± 11.5 beats/min, p = 0.04), cardiac index (1.6 ± 1.0 l/min/m2 vs. 0.8 ± 1.1 l/min/m2, p = 0.03), and LV ejection fraction (7.1 ± 4.0% vs. 2.9 ± 4.4%, p = 0.003) were greater in younger than older subjects, respectively, as was the reduction in ESVI (−5.1 ± 3.0 ml/m2 vs. −1.8 ± 3.3 ml/m2, p = 0.002), despite similar declines in systolic BP (−12.3 ± 6.3 mm Hg vs. −12.1 ± 15.0 mm Hg, p = NS). Thus, age-associated deficits in chronotropic and LV systolic reserve performance occur during prolonged submaximal upright cycle ergometry, analogous to those observed during graded maximal exercise.